'Thou shalt not kill': a survey experiment on the effects of moral primes on war attitudes in Turkey. (19th October 2020) - Kiratli, Osman Sabri
ABSTRACT: Through an original survey experiment on a nationally representative sample of the Turkish population, this article demonstrates that respondents who are primed on the immorality of the use of force against others are substantially more willing to support only conditional military intervention in a civil war in another country. Further statistical analyses reveal that the activation of moral beliefs largely depends on the degree of approval of the moral statement and previously held foreign policy predispositions on isolationism. These findings contribute to the research on priming and public opinion regarding the use of force in general and, in particular, interventions in civil wars.